Segmentation of ethnic tourists and their interaction outcomes with hosts in the Central Highlands, Vietnam - Nguyễn, Thị Thanh Kiều (Calla) (2024)
Emphasizing interactions with ethnic minority hosts, this paper segments domestic tourists visiting Vietnam’s Central Highlands based on their travel motivation. Three PERSONAS summarize profiles of Explorers, Seekers, and Enjoyers based on their socio-demographic and trip characteristics, especially differences in host-tourist interactions and perceptions of ethnic tourism outcomes. Such data informs decisions about what type of tourists villagers want to serve to achieve community aspirations. Explorers and Seekers were identified as the most suitable target groups to attain better interaction out-comes and make positive contributions to the local community. Tourism marketers and policymakers can use PERSONAS to develop campaigns to attract the targeted segments.